Forging Temperature Effects on Crack Tip Creep Behaviour of Hot Hammer Forged Ti-6Al-4V Alloy. (23rd January 2023) - Fang, Xiurong; Liu, Yan; Shao, Yanru; Xu, Huihui; Yang, Fuqiang
Abstract : The creep behaviour of hot hammer forged Ti-6Al-4V alloy under different forging temperatures has an essential influence on their high-temperature service performance. In this article, the high-temperature mechanical property and creep behaviour of Ti-6Al-4V alloy forging at different forging temperatures were first investigated experimentally. Then, in view of the critical effect of microcracks and other defects on the service life of components in forging, the creep characteristics at the tip of a 2 mm crack were characterized by the finite element method. The results show that when the Ti-6Al-4V alloy was forged at 1000°C, the high-temperature mechanical property was improved, and the steady-state creep rate and creep residual deformation were significantly reduced. In addition, the creep strain and creep rate at the crack tip were decreased apparently during creep, and the creep strain gradient in the crack tip region was also significantly reduced. This indicates that the creep deformation of Ti-6Al-4V alloy can be controlled by an appropriate forging temperature during hot hammer forging process and might delay the crack propagation to improve the service life of components.